2021
DOI: 10.1038/s12276-021-00714-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals B cell–related molecular biomarkers for Alzheimer’s disease

Abstract: In recent years, biomarkers have been integrated into the diagnostic process and have become increasingly indispensable for obtaining knowledge of the neurodegenerative processes in Alzheimer’s disease (AD). Peripheral blood mononuclear cells (PBMCs) in human blood have been reported to participate in a variety of neurodegenerative activities. Here, a single-cell RNA sequencing analysis of PBMCs from 4 AD patients (2 in the early stage, 2 in the late stage) and 2 normal controls was performed to explore the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…In the immune infiltration analysis, RPL36AL was mainly on B cells. Single-cell RNA sequencing reveals significant decrease in B cells detected in blood of AD patients, and similar studies have previously yielded similar results (18).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the immune infiltration analysis, RPL36AL was mainly on B cells. Single-cell RNA sequencing reveals significant decrease in B cells detected in blood of AD patients, and similar studies have previously yielded similar results (18).…”
Section: Discussionsupporting
confidence: 80%
“…Dataset acquisition, processing and differential expression analysis GSE63060 ( 17), GSE63061 and one AD single-cell RNAsequencing dataset GSE168522 (18); the same method was used to obtain the MetS dataset GSE (19). The software R (https://www.bioconductor.org/) was used for data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…3C) and also limited overlap with those identified from single-cell RNA sequencing datasets (Additional file 1: Fig. S13) [38,40,78], which may due to the differences of sample preparation, sequencing methods, and analytic protocols, as well as the heterogeneity of the participants. However, there was a convergence in dysregulated signaling pathways, such as the dysregulations of regulation of defense response, cellular response to cytokine stimulus, and regulation of inflammatory response in the majority of cell types, suggesting that pathway and network-based markers may be more robust [95].…”
Section: Discussionmentioning
confidence: 99%
“…Activated CD8 + T cells exhibit a higher proportion in the CSF of AD patients than healthy older adults and correlate with clinical and structural markers of AD pathology [37]. Several studies based on the single-cell RNA sequencing of peripheral blood mononuclear cells further have disclosed the cell-specific signatures in AD and mild cognitive impairment (MCI) [38][39][40]. However, the small sample size and underestimate of polymorphonuclear leukocytes (e.g., neutrophils) limit our understanding of the distribution and biological characteristics of all the peripheral blood immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we could also speculate through the results from Figure 7 that changes in the B cell population and their secretion of IgG are related to brain microglial function regulating the expression of TGF-b in microglia (Li et al, 2017;Taylor et al, 2017). Since there is still debate that the decrease in the B cell population alleviates or exacerbates the deposition of Ab (Kim et al, 2021;Xiong et al, 2021), our acute or chronic models for Ab can partially explain this controversy in terms of microglial responses to IgG in the brain. In particular, our results correspond to those of Kim et al, who showed the therapeutic effect of B cell depletion through restoration of TGF-b in microglia (Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 92%